Geography of Ebola virus. Socio-Spatial Issues in Central Africa. Outlook for West Africa - (:unkn) unknown (My University, 2015)
On April 15, 2015, the West African Ebola outbreak, for nearly one year, affected 25 791 persons and caused 10 689 deaths. Between 2005 and 2010, we conducted a research, as part of a thesis, on anthropogenic factors of emergence and spread of Ebola virus haemorrhagic fever - EVHF. In this text, we intended to compare the two health crises, in order to highlight the processes that participate in making EVHF outbreaks. We primarily want to show that these crises remain primarily social crises. Those globalized health crises pin point the North-South relations and show how crisis management can induce breaks in communications between health workers and patients. These breaks are participating in the protest of the poorest populations and sustainable reconfiguration of territories after the crisis. Finally, we want to highlight the lessons learned from earlier outbreaks and recommend, their recognition by the actors, to improve the fight against coming epidemics. Regardless of context, social processes at work in all Ebola outbreaks seem recurrent.
Keywords: African Research